Foundations of Genetic Programming - William B. Langdon (Springer, 2001)
1. Introduction -- 2. Fitness Landscapes -- 3. Program Component Schema Theories -- 4. Pessimistic GP Schema Theories -- 5. Exact GP Schema Theorems -- 6. Lessons from the GP Schema Theory -- 7. The Genetic Programming Search Space -- 8. The GP Search Space: Theoretical Analysis -- 9. Example I: The Artificial Ant -- 10. Example II: The Max Problem -- 11. GP Convergence and Bloat -- 12. Conclusions.